Effect of Puzzle Playing Therapy on Stress Levels Hospitalization for Children (4-6 Years) - Rahmawati, Eva Silviana; Nuraini, Nanik (Universitas Islam Lamongan, 2023)
Aggressive reactions with anger and rebellion, verbal expressions with angry words, do not want to cooperate with nurses, if this condition occurs it will affect the treatment process while in hospital (Supartini, 2004). For that, children need media to divert reactions aggressive. The purpose of this study was to determine the effect of puzzle play therapy on hospitalization stress for children (4-6 years) in the Melati Room, RSID dr. R. Koesma Tuban. This study used a One Group Pre -Post Test design which involved 19 respondents who were taken by Systematic Random Sampling. Data was taken using a questionnaire. Data were analyzed using the Wilcoxon test with a significant level of 0.05. The results showed that H 0 was rejected, so that there was an effect of puzzle playing therapy on the level of stress hospitalization children (4-6 years old ) in the Jasmine Room Hospital d r. R. Koesma Tuban ( Asymp value Sig. (2- tailed ) = 0.000 ). Puzzle play therapy has been shown to reduce the level of stress hospitalization children aged 4-6 years. The hospital should provide a special room for children to play, socialization to health workers, especially nursery nurses, such as being given puzzle play therapy, as well as providing rooms designed for children. Asking for parental support, assistance and participation is also needed so that puzzle play therapy can be implemented properly.